PENINGKATAN UKURAN LINGKAR PINGGANG SEBAGAI FAKTOR RISIKO STROKE DI RSUP DR SARDJITO - , NISA AMANITA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Obesity has lately been one of the condition that affect health the most and related closely to vascular diseases. Abdominal obesity, which can be measured by waist circumference, correlate to hypertension and diabetes, which these 2 are the risk factor for stroke. Aim: to find whether large waist circumference is the risk factor for stroke Methods: This research uses case-control design. Subjects are patients in Poli Saraf and Stroke Unit RSUP Sardjito. Diagnoses based on medical record, waist circumference measured on the spot, obesity state based on IDF criteria Result: Obese subjects are much more in case group (12) and non-obese subjects are much more in control group (14). On data analysis, OR=3,5 (95%CI: 0,94-12,97). This means that obese subjects have more chance to get stroke by 3,5 Conclusion: a large waist circumference have greater chance to get stroke by 3,5: but statistically not a risk factor.